Facilitating teachers’ inclusive education intentions: the roles of transformational leadership, school climate, and teacher efficacy - Tiantian Wang; Meng Deng; Guoxiu Tian (Humanities & Social Sciences Communications)
Abstract Teacher intention toward employing inclusive practices is pivotal to determining instructional behaviors and teaching effectiveness of inclusive education. Although previous research evidenced that some individual antecedents such as self-efficacy predict teachers’ inclusive education intentions, few studies pay due attention to the integration of organizational and individual contributors to such intentions, especially in Mainland China. A cross-sectional study was conducted to investigate teacher intention to implement inclusive practices and its relationship to two types of facilitating factors: organizational (i.e., transformational leadership and school inclusion climate) and individual (i.e., teacher efficacy) in the context of mainland China. Structural equation modeling examining the direct and mediating influences was carried out among a sample of 780 teachers in Beijing, China. Research findings indicated that principal transformational leadership significantly predicted teachers’ inclusive education intentions directly and indirectly through school inclusion climate and teacher efficacy for inclusion. Teachers with higher inclusive efficacious beliefs exhibited more positive intentions to teach inclusively. The results stressed the significance of creating organizational conditions for inclusion and elevating the inclusive practitioners’ efficacy beliefs in inclusive schools. Possible explanations and implications were represented.